1993
DOI: 10.1111/j.1365-3121.1993.tb00306.x
|View full text |Cite
|
Sign up to set email alerts
|

238U‐series disequilibrium in the Upper Cretaceous oil shales of Israel as the primary source for the Dead Sea's 226Ra anomaly

Abstract: The Dead Sea contains an anomalously high concentration of soluble radium, which is considerably in excess of its radiogenic parent uranium. Mass balance calculations demonstrated that the radium is brought to the Dead Sea by springs and shallow underground seepages. The primary source from which this radium-excess is derived has not been identified previously. Using a combination of alpha-spectrometry, delayed neutron activation (DNA), and gamma-ray spectrometric analyses, it was found that the extensive oil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
2
4
0
Order By: Relevance
“…The alpha-spectrometric analysis showed that neither U nor Th had been leached, as the 234 U/ 238 U and 230 Th/ 234 U active ratios were at secular equilibrium. This is consistent with similar analyses (Kronfeld et al, 1993) of oil shale in southern Israel. It can be seen that strong discrepancies are encountered (pronounced in the organic rich layers) between the two techniques that are well beyond any statistical counting fluctuations.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The alpha-spectrometric analysis showed that neither U nor Th had been leached, as the 234 U/ 238 U and 230 Th/ 234 U active ratios were at secular equilibrium. This is consistent with similar analyses (Kronfeld et al, 1993) of oil shale in southern Israel. It can be seen that strong discrepancies are encountered (pronounced in the organic rich layers) between the two techniques that are well beyond any statistical counting fluctuations.…”
Section: Resultssupporting
confidence: 92%
“…In borehole AB-8 located on the shore of the lake (coordinates 19916/24674, Israel grid, 89 m deep) most of the penetrated sequence is composed of oil shale. Correlative oil shale sequence has been previously shown elsewhere in Israel to yield their Ra (but no U or Th) to intruding, moderately saline water (Kronfeld et al, 1993;Minster et al, 2004).…”
Section: Introductionmentioning
confidence: 89%
“…Uranium-238 concentrations in rock from Niigata Prefecture were similar to those of carbonate and shale from the Central US (5.1-52 mBq g À1 by Sturchio et al, 2001) and of sandstone and shale from the US Gulf Coast (4.6-42 mBq g À1 by Kraemer and Reid, 1984). Oil shale from the Dead Sea Valley had much higher 238 U contents over 1000 mBq g À1 (Kronfeld et al, 1993;Ilani et al, 2006). It is expected that 226 Ra concentration in water would increase as 238 U contents of surrounding rock are higher.…”
Section: Comparison With Other Saline Watersmentioning
confidence: 65%
“…If 226 Ra in Na-Cl type groundwater were derived from uraniferous rock with low 232 Th/ 238 U activity ratios, the 228 Ra/ 226 Ra activity ratios would be expected to become very lower (as discussed later). In fact, most measurements of groundwaters from the Dead Sea Valley had typically low 228 Ra/ 226 Ra activity ratios (minimal value of 0.03 by Moise et al, 2000) and this is considered to be due to the uraniferous rock including oil shale (Kronfeld et al, 1993;Ilani et al, 2006). Most of the Na-Cl type groundwater samples measured here had relatively higher Ra/ 226 Ra activity ratios than 232 Th/ 238 U activity ratios in oil shale reported and 228 Ra/ 226 Ra activity ratios in groundwaters from the Dead Sea Valley, although sample N13 had the lowest 228 Ra/ 226 Ra activity ratio (0.32) with high Ba concentration in the absence of SO 4 .…”
Section: Radium and U Isotope Concentrations And Their Activity Ratiosmentioning
confidence: 99%
See 1 more Smart Citation